Compreensão do mentir em contexto brasileiro a partir de sua relação com variáveis psicológicas - Meneses, Glysa de Oliveira (2021)
Deceive and being deceived are probably some of the most frequent behaviors observed in everyday life. Lying, far from being something unusual or atypical, is a fact of everyday life, with adaptive functions. Due to the multifaceted characteristic of lying, several studies were conducted to improve knowledge about this behavior, based on the processes involved in its manifestation. This doctoral thesis aimed to understand the lying behavior based on its relationship with psychological variables in the Brazilian context: the Brazilian jeitinho, empathy, lie acceptability and human values. Two empirical studies were conducted. Study I sought to develop a comprehensive measure to assess lying behavior, named Lies’ Scale, and to adapt the Lie Acceptability Scale to the Brazilian context. Evidence of validity and internal consistency of the instruments was also evaluated. A total of 152 people, aged between 18 and 70 years old (M = 27.8; SD = 8.17) participated. The results indicated satisfactory evidence of validity and reliability for both measures. Study II aimed to understand the relationship between psychological variables and lying behavior in Brazil. In step I, the associations between the Brazilian jeitinho, empathy, acceptability of lies, human values and antisocial and prosocial lies were analyzed. Participants were 212 adults, aged between 18 and 66 years old (M = 28.90; SD = 8.50), who responded to the two instruments developed in Study I, in addition to the Personal Jeitinho Scale; the Interpersonal Reactivity Index, the Basic Values Survey and a sociodemographic questionnaire. In step II, comprehensive models for lying behavior were tested, considering the two types of lies and the relationship between them and the psychological variables, based on the results verified in the previous step. 633 people participated, whose ages ranged between 18 and 68 years old (M = 26.64; SD = 7.63), who responded to the same measures used in step I. For antisocial lies, it was found that the most appropriate model included the lie acceptability and personal values as partial mediators of the relationship between the jeitinho malandro and the frequency of antisocial lies. For prosocial lies, the most appropriate model included empathy as a partial mediator of the relationship between the jeitinho simpático and the frequency of this type of lie directly correlated with the lie acceptability. Despite the limitations, it is believed that this thesis achieved its main objective by providing a better understanding of lying in Brazil, providing advancements to the investigation of this construct. Furthermore, it provided two measures to assess lying behavior in Brazilian Portuguese with good psychometric properties.